Sensibilidade e especificidade do desempenho no salto vertical para triagem de sarcopenia em idosos - Santos, Layla Maciel dos (2024)
Neuromuscular declines inherent to aging, when reaching a certain threshold, can characterize a condition of sarcopenia, which is a musculoskeletal disease characterized by low levels of muscle strength and mass, potentially impairing physical performance in severe cases. Various tests and algorithms have been validated for the diagnostic assessment of sarcopenia. However, muscle power, a variable that declines sharply with aging, has not been considered. The vertical jump is an assessment capable of estimating muscle power, and its performance is associated with the three neuromuscular parameters that characterize sarcopenia. The aim of the present study was to analyze the sensitivity and specificity of vertical jump performance, assessed through an application for sarcopenia screening in older adults. A cross-sectional design was applied, with male and female participants aged 60 years or older, capable of performing the vertical jump with countermovement. Sociodemographic data and health history were obtained through questionnaires, as well as the assessment of participants' weekly physical activity levels. European Working Group on Sarcopenia in Older People – EWGSOP2 consensus was applied for the diagnosis of sarcopenia, including the assessment of muscle strength through handgrip strength tests and the five-times chair stand test. Muscle mass was assessed using an estimation equation. For the analysis of jump performance, video recordings of jump height were made using the My Jump app. Muscle power was also analyzed through estimation equations for both the jump values and the five-times chair stand test. A total of 214 elderly participants took part, mostly women (84.6%), Caucasian (43.9%), and physically active (535.21 ± 558.59 minutes/week). The prevalence of sarcopenia was 4.7%, and the prevalence of probable sarcopenia was 25.7% according to the EWGSOP2 algorithm. Performance in vertical jump height demonstrated high specificity (92.57%) and low sensitivity (50.0%) for sarcopenia screening, while jump power relative to body mass yielded better results (Se=90%, Sp=82.18%, and AUC=0.9146). Therefore, for sarcopenia screening in older adults, an effective assessment that can be included is vertical jump power.